Rex Nettleford : his works : an annotated bibliography 1950-2004 - Jefferson, Albertina (The Press UWI MonaJM)
Captures fifty-four years of Rex Nettleford's efforts to liberate the Caribbean, and indeed the world, from the shackles of 'mental slavery'. Covers published and unpublished works. Includes his choreography for the National Dance Theatre Company of Jamaica and the Little Theatre Movement Pantomine. Provides a chronology of bio-data of Nettleford's life and achievements.